Voltammetric analysis of mephenoxalone drug in pharmaceutical and biological samples using novel screen-printed sensor with boron-doped diamond electrode - Matvieiev, Oleksandr; Šelešovská, Renáta; Sokolová, Romana; Jerga, Radek; Skopalová, Jana; Barták, Petr; Chýlková, Jaromíra; Vojs, Marian (My University, 2023)
A novel screen-printed sensor (SPE) with boron-doped diamond electrode (BDDE) for determination of a muscle relaxant and mild anxiolytic mephenoxalone (MNL) was developed. The sensor utilizes the electrochemical oxidation of MNL, which was firstly studied in aqueous solution using oxygen terminated BDDE. MNL provided an irreversible anodic signal at a potential of + 1380 mV (vs. Ag/AgCl/KCl sat.) over a wide pH range. BrittonRobinson buffer (pH 9) was selected as a suitable electrolyte and the square-wave voltammetric method (SWV) was developed. The low detection limit (55 nmol L–1), wide linear dynamic range (0.1–30 µmol L− 1), and good recovery in the analysis of model and pharmaceutical samples (RSD < 1.77%) were attained. Subsequently, the new method was successfully transferred to SPE, which can find application in point-of-care testing. These sensors proved excellent sensitivity and reproducibility in the analysis of biological samples (RSD < 4.94%) without pretreatment and no need of electrolyte. Based on gas chromatography with mass spectrometry (GC-MS) analysis of preparative electrolysis products, a mechanism of the electrochemical oxidation of MNL was proposed, describing the oxidative cleavage of the alkoxybenzene ring. These results were supported with HOMO spatial distribution calculations and atomic charges calculations for arising radical cations, and with spectroelectrochemical measurements.
Voltametrická analýza mefenoxalonového léčiva ve farmaceutických a biologických vzorcích pomocí nového sítotiskového senzoru s borem dopovanou diamantovou elektrodou
Keywords: Mephenoxalone; Voltammetry; Screen-printed sensor with boron-doped diamond electrode; GC-MS analysis; Spectroelectrochemistry; Mefenoxalon; Voltametrie; Sítotiskové senzory s borem dopovanou diamantovou elektrodou; GC-MS analýza; Spektroelektrochemie